Penekanan Pertumbuhan Gulma Melalui Sistem Tumpangsari Jagung Manis dengan Kacang-Kacangan di Pertanian Organik - A. Prakoso; U. Nurjanah; Widodo Widodo; N. Setyowati; Prasetyo Prasetyo (Seminar Nasional Lahan Suboptimal, 2020)
Prakoso A, Nurjanah U, Widodo W, Setyowati N, Prasetyo P. 2020. Weed growth emphasis through intercropping system of sweet corn with legumes in organic farming. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).One of the weed control technologies that are environmentally friendly and require little cost is technical culture such as intercropping planting. The aim of this study was to determine the combination of the planting intercropping sweet corn with legumes and the planting time of legumes which effectively suppresses weed growth. The research was conducted from August to November 2019 in Air Duku Village, Selupu Rejang District, Rejang Lebong Regency, Bengkulu at an altitude  ± 1051 masl. The study used a non-factorial completely randomized block design (RAKL) with three replications. The treatment applied was an intercropping system of sweet corn with peanuts, soybeans, and  long beans planted at 15, 10, 5, and 0 days before planting sweet corn. Observed variable data were collected and analyzed using analysis of variance (ANOVA) level of 5%. The observed weeds were analyzed by the Summed Dominance Ratio (SDR). The results showed that Cyperus rotundus L. weed was dominant at 3 and 6 weeks after planting with SDRs of 57.12% and 55.53%. The weed dominance of C. rotundus L. was replaced by Sacciolepis interrupta at harvest time with SDR = 48.42%. Peanuts planted 15 days before planting sweet corn were the best treatment in suppressing weed growth based on the largest total dry weight emphasis (84.59%), and the lowest weed population number, namely 2.65 individuals. The highest growth and yield of sweet corn were peanuts planted simultaneously with sweet corn, long beans planted 5 days before sweet corn, and soybeans planted simultaneously with sweet corn.